Etyczne wyzwania w przemyśle farmaceutycznym. Zarys problematyki - Kaczmarek, Emilia (Annales. Etyka w Życiu Gospodarczym, 2015)
The goal of the text is to show which actions of the modern pharmaceutical industry are morally controversial. There are several burning issues that we need to face on this field, such as: How to deal with the conflict of interests within the medicine? How to mark the vanishing boundaries between information and advertisement concerning the pharmaceutical education? How does the drug advertisement lead to the pharmaceuticalization of society? In the text all of these problems will be briefly analysed. The article has an introductory character, it may serve as an overview of the burning issues in the pharmaceutical industry ethics – all questions that are posed in the text need further examination.